2009
DOI: 10.1016/j.brainres.2009.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture mobilizes the brain's default mode and its anti-correlated network in healthy subjects

Abstract: Previous work has shown that acupuncture stimulation evokes deactivation of a limbic-paralimbic-neocortical network (LPNN) as well as activation of somatosensory brain regions. This study explores the activity and functional connectivity of these regions during acupuncture vs. tactile stimulation and vs. acupuncture associated with inadvertent sharp pain. Acupuncture during 201 scans and tactile stimulation during 74 scans for comparison at acupoints LI4, ST36 and LV3 was monitored with fMRI and psychophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 81 publications
10
118
2
Order By: Relevance
“…Both treatment modalities activate endogenous pain inhibitory systems, however they are believed to act through different mechanisms. 17 …”
mentioning
confidence: 99%
“…Both treatment modalities activate endogenous pain inhibitory systems, however they are believed to act through different mechanisms. 17 …”
mentioning
confidence: 99%
“…25 It has been reported that SI processing is performed with input provided by mechanoreceptors, 26 but the activation of much of the SI has not been conˆrmed by acupuncture stimulation. 1,2,[4][5][6][7][8][10][11][12][13][14] The peripheral receptors involved in acupuncture stimulation have been suggested to be the polymodal receptors that are nociceptive receptors of the C-ˆbers. 27 It is also thought that the input is the transmission through C-ˆber in response to production of a chemical substance following deep tissue injury by manual acupuncture stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, the development of imaging techniques, such as functional magnetic resonance imaging (fMRI), has opened the door for the study of brain activity in response to acupuncture stimulation. Numerous studies have been performed with fMRI and a variety of acupuncturerelated stimulations, such as electroacupuncture, 1,2 manual acupuncture, [1][2][3][4][5][6][7][8][9][10][11][12][13] sham acupuncture of the skin some distance from a known acupoint [4][5][6] or by noninsertive acupuncture and poking of the skin over an acupuncture point, [7][8][9][10][11] pressure to the acupoint, 12 laser acupuncture, 13 and electrical acupoint stimulation. 14 fMRI studies of acupuncture have typically utilized a block design that is used as a general linear model regressor in the analysis of fMRI data based on the assumption that mechanoreceptors and nociceptor-associated aŠerence work coincidentally with acupuncture stimulation, which is the conscious perception and evaluation of this aŠerence.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, a common factor in these two treatments was the nociceptive afferents. Pain (from nociceptors) has been shown to elicit activation of the sensorimotor cortices, rostral anterior cingulate cortex, insula, cerebellum, hippocampus and brain stem Hui et al, 2009;Kong et al, 2007;Lewith et al, 2005;Seidler et al, 2004) through spinothalamus bundle. A number of cortical areas have been shown to be involved in pain processing, including the primary somatosensory cortex, the secondary somatosensory cortex, the insula, the anterior cingulate, the prefrontal cortex, the hypothalamus and periaqueductal gray (PAG) (Kong et al, 2009;Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%